Supply Chain Model in Digital for Cooperative Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The objective of the research was to design and to evaluate an appropriate of supply chain model in digital for cooperative management in Thailand. The sample consisted of ten experts that were selected by simple random sampling .Data analysis was the average mean and standard deviation. The research tool was questionnaire about supply chain model in digital for cooperative management in Thailand comprises seven main components, namely suppliers, Cooperative, Distribution, Retailers, customer, feedback. The results from experts agreement of supply chain model in digital for cooperative management in Thailand was a high level which means that supply chain model in digital for cooperative management in Thailand can be appropriately applied in actual work settings.